(untitled) (Journal of Contemporary Philology, 2020)
This study examines the role of metaphor in the conceptualization of hope (nada) in the Croatian corpus hrWaC. Employing “metaphorical pattern analysis” (Stefanowitsch, 2006), I analyze metaphorical patterns with the target-domain word nada ‘hope’. These patterns were extracted from a random sample of 1000 citations and additional citations retrieved based on the collocation candidates’ list. The analysis shows that the conceptualization of hope in Croatian relates to approximately fifty metaphorical source domains. The most frequently utilized are object, container, and companion, which apply to many other emotions, dispositions, and states. The study builds on relevant research questions and findings on the conceptual representation of emotions and metaphors structuring emotions within cognitive linguistic research. It offers a basis for future qualitative studies about hope as a universal and culture-specific concept.